Sistem Pakar Diagnosis Penyakit Hati Menggunakan Metode Fuzzy Tsukamoto Berbasis Android - Achmad Igaz Falatehan; Nurul Hidayat; Komang Candra Brata (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
The liver is a vital organ in humans. Because the vital liver function, the liver health needs to be maintained. However, in Indonesia alone, especially Hepatitis liver disease based on survey from the health ministry actually has doubled from 2007 to 2013. In 2013, it is estimated that there are 1.2% of Indonesians who suffer from Hepatitis. Based on WHO survey It is estimated 95% of people with early symptoms of Hepatitis do not know that they are at risk of Hepatitis. The mentioned problems can be solved by recognizing the common symptoms of liver disease. The problem of recognizing the symptoms of liver disease can be solved by using an expert system. Expert systems apply knowledge of symptoms liver disease into the system. The Fuzzy Tsukamoto method is one of the methods that can be used to process the input value of symptoms into a disease diagnosis. In this research will use Fuzzy Tsukamoto method to diagnose liver disease based on input value of the symptoms that produce output of detected yes or not a liver disease. Based on the results of tests that have been done in this study resulted in accuracy testing of 64 test data 96,87%.